Unravelling the Central American borders through geography: interview with Lucile Medina - Medina, Lucile (2024)
This is an interview made by Dr. Tania Rodríguez to Dr. Lucile Medina, a french geography expert and researcher on border dymanics. In this manuscipt, Dr. Medina discusses about her academic background and how her research was redirected towards the Central American territory. The interviewee emphasizes the importance of expand the geographical border definition beyond the geometric delineation by considering a more interpretative point of view, where borders are more than divisions and incoporate multidisciplinary perspectives. In essence, for Dr. Medina, the traditional border definition falls short to explain the multiple dynamics unfolding in the nearby territories, which are constantly transforming and suffer of highly porous interactions. Lastly, she concludes with an evaluation of the current border dynamics and how what once was characterized by an opening of borders through community collaboration is now transforming into a negative cooperation towards closure due to the involvement of the governments.